THE INITIATION OF THE PROCESS AND THE PROOF IN THE RUSSIAN INVESTIGATIVE PROCEEDINGS IN THE SECOND HALF OF XVII - BEGINNING OF XVIII CENTURIES - L. Batiev (Гуманитарные и юридические исследования)
Investigative proceedings were initiated mainly on the initiative of oficials. The reasons were: oblihovanie pov-al'nym obyskom", "jazychnaja molka ", "izvet", capture at the scene, capture of suspicious characters, «gonenie sle-da», feudal lords (or a clerk) bringing their peasants on spe-ciic charges of robbery, etc., «donos iskala» , identifying offenses during the trial, prosecutor's supervision ... Means of initiating investigative proceedings also remained the plaintiffs petition («chelobytnaya»). But the plaintiff's impact on the inquisitorial proceedings was reduced. Traditional means of proof (in addition to a confession by the accused) did not have absolute power. Grounds for initiation of the case was at the same time means of proof. The burden of proof lay primarily on the defendant. The deini-tive of proof was confession. Confession during torture was sufficient for allegations and for the application of sanctions in full. Denial («zapiratel'stvo») on "rosprosy" and torture did not have deinite values. Witness testimonies were traditionally taken in two basic forms: the "ssylka iz vinovatyh" and "obshhaja ssylka". They were decisive, either in favour of the side, which referred to them, or for both sides. The court usually sought the opinions of the parties and from a variety of witnesses gave preference to "obshhej ssylke". "Polichnoe" was suficient grounds for compulsory (after «raspros») recourse to torture. "Jazychnaja molka" - accusation of third parties during the process, or within the first two weeks of the sentence, or at the execution. "Jazyk" at the confrontation had to identify the accused and conirm the «ogovor». "Poval'nyj obysk" -one of the most common means of proof. However, already in the 17th century we can see the decrease of the search importance. The objective of "obshhij poval'nyj obysk" was identiication of "vedomye lihie ljudi" in the county through the population survey; the objective of "special'nyj obysk" was to establish certain facts or the reputation of a particular person already involved in the search. "Obshhij pov- al'nyj obysk" gradually disappeared. The scope of use of the "special'nyj obysk" (its task was the establishment of a fact) was reduced, it gradually merged with the testimony and was replaced by them. Judicial research was carried out by direct observation by the court of the case, written documents, etc. The most important means of investigation remained torture. Its goal was the confession of the defendant, identifying accomplices, amount of stolen property, clarifying the intent.